2022
DOI: 10.1007/s10340-022-01485-5
|View full text |Cite
|
Sign up to set email alerts
|

A first greenhouse application of bacteria-expressed and nanocarrier-delivered RNA pesticide for Myzus persicae control

Abstract: There are two main limitations for sprayable RNA pesticide development: delivery e ciency and synthetic cost of double-stranded RNA (dsRNA). We previously constructed a nanocarrier-based transdermal dsRNA delivery system and a novel bacteria-based hairpin RNA (hpRNA) expression system to solve these challenges. Herein, as a subsequent exploration of RNA pesticide (sprayable ds/hpRNA for pest control), we performed a greenhouse application of bacteria-expressed and nanocarrier-delivered RNA pesticide on green p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 57 publications
2
39
0
2
Order By: Relevance
“…The dead aphids caused by various formulations exhibited dehydration and turned to black on tobacco leaves ( Figure S3 ). According to the previous studies [ 10 , 13 ], the dropping rate of aphids treated with imidaclothiz/SPc complex was significantly higher than that of imidaclothiz, and the control efficacy of imidaclothiz/SPc complex could reach 76.75% (4 d) and 81.91% (6 d) compared with 39.84% (4 d) and 47.90% (6 d) in imidaclothiz treatment ( Figure 5 A,B). National standard (grade and investigation method of tobacco diseases and insect pests, GB/T 23222-2008) was also used to analyze the control efficacy.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The dead aphids caused by various formulations exhibited dehydration and turned to black on tobacco leaves ( Figure S3 ). According to the previous studies [ 10 , 13 ], the dropping rate of aphids treated with imidaclothiz/SPc complex was significantly higher than that of imidaclothiz, and the control efficacy of imidaclothiz/SPc complex could reach 76.75% (4 d) and 81.91% (6 d) compared with 39.84% (4 d) and 47.90% (6 d) in imidaclothiz treatment ( Figure 5 A,B). National standard (grade and investigation method of tobacco diseases and insect pests, GB/T 23222-2008) was also used to analyze the control efficacy.…”
Section: Resultsmentioning
confidence: 57%
“…Two methods were used to calculate the control efficacy. (1) According to the previous studies [ 10 , 13 ], the dropping rate of insect (DRI) and control efficacy (CE) were calculated using the formulas of DRI (%) = (aphid number before pesticide application − aphid number after pesticide application) ÷ aphid number before pesticide application × 100% and CE (%) = (DRI in the treatment plot − DRI in the control plot) ÷ (100 − DRI in the control plot) × 100%. (2) According to the national standard (grade and investigation method of tobacco diseases and insect pests, GB/T 23222-2008), the plants infested with aphids were classified.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary effector Bt56 in whiteflies B. tabaci was silenced by feeding with artificial diet containing dsRNA, resulting in significantly reduced whitefly performance on host plants and shorter phloem feeding durations [43]. Nanocarrier-mediated RNAi is a practical delivery system for silencing target genes of hemipteran insects, such as soybean aphid Aphis glycines and M. persicae, and is considered a promising strategy for gene function characterization and pest control [44][45][46]. In this study, to further examine the roles of Sm9723 on S. miscanthi fitness, the Sm9723 gene was silenced following application of the nanocarrier-mediated transdermal dsRNA delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes suggest Sm9723 is essential for aphid adaptability to host plants as a salivary effector. Spray application of dsRNA pesticide shows great potential in controlling M. persicae and several plant pathogens [46,47]. Further, previous studies demonstrated that host induced gene silencing (HIGS) in transgenic wheat and barley plants targeting essential genes of S. avenae can successfully confer resistance against aphids [48,49].…”
Section: Discussionmentioning
confidence: 99%